The power of solvent in altering the course of photorearrangements - Šebej, Peter; Lim, Bum Hee; Park, Bong Ser; Givens, Richard S; Klán, Petr (Organic letters, 2011)
A clean bifurcation between two important photochemical reactions through competition of a triplet state Type II H-abstraction reaction with a photo-Favorskii rearrangement for (o/p)-hydroxy-o-methylphenacyl esters that depends on the water content of the solvent has been established. The switch from the anhydrous Type II pathway that yields indanones to the aqueous-dependent pathway producing benzofuranones occurs abruptly at low water concentrations (~8%). The surprisingly clean yields suggest that such reactions are synthetically promising.
Keywords: Benzofurans; Photochemical Processes; fotochemické procesy; Water; benzenové deriváty; Esters; Indans; Benzene Derivatives; Solvents; benzofurany; indany; voda; rozpouštědla; estery